King of comedy the life and art of Jerry Lewis - Levy, Shawn 1961- (St. Martin's Press, 1996)
A biography of Jerry Lewis, discussing his varied career as a performer, director, fundraiser, and standard-setting comedian, and looking at the private man and the forces that drive him.
Keywords: Lewis, Jerry <1926->; Lewis, Jerry -- 1926-2017; Comedians -- United States -- Biography; USA; Biografie